Medical Services, Patient Age, and Level of Education on Its Influence on Diabetic Patients’ Level of Satisfaction - Erich P. Ea; Megan B. Lipura; Benj Enrick R. Halaghay; Lanz Alfred G. Tugom (Universitas Pendidikan Indonesia (UPI), 2023)
According to the Department of Health, diabetes is among the main causes of death among Filipinos. As a result, medical administrations must provide high-quality services. Patients, treatments, and particularly rural medical centers should all receive adequate screenings from the government. The goal of this study is to find out how satisfied diabetic patients are with the medical care they receive. Twenty-two (22) people with diabetes were included in the study. A survey will be utilized to gather information and data from a group of diabetic patients. The results show that: (1) there is no substantial difference in diabetic patients' satisfaction based on sex demographics; (2) there is no substantial difference in diabetic patients' satisfaction based on age demographics; (3) there is also no substantial difference in diabetic patients' satisfaction based on the establishment; and (4) there is a substantial difference between the patient's satisfaction and the medical services offered. When it comes to the score mean, diabetic patients' satisfactions are inside the extremely satisfied verbal description. The majority of the respondents were between the ages of 47 and 54. 12 females, 10 males, and 15 of them were in one medical establishment and the others were in the second. Despite their demographic differences, their satisfaction levels were quite close. Since there is a significant difference between the medical services dimension and the mean score of the overall medical structure and process is lower, there is a slight improvement for the medical establishments to focus on the medical structure and process, specifically the facilities, transportation convenience, and the length of waiting which the patients scored lower than the other parameters.